Bone Loss After Bariatric Surgery: Discordant Results Between DXA and QCT Bone Density. (March 2014) - Yu, Elaine W; Bouxsein, Mary L; Roy, Adam E; Baldwin, Chantel; Cange, Abby; Neer, Robert M; Kaplan, Lee M; Finkelstein, Joel S
ABSTRACT Several studies, using dual‐energy X‐ray absorptiometry (DXA), have reported substantial bone loss after bariatric surgery. However, profound weight loss may cause artifactual changes in DXA areal bone mineral density (aBMD) results. Assessment of volumetric bone mineral density (vBMD) by quantitative computed tomography (QCT) may be less susceptible to such artifacts. We assessed changes in BMD of the lumbar spine and proximal femur prospectively for 1 year using DXA and QCT in 30 morbidly obese adults undergoing Roux‐en‐Y gastric bypass surgery and 20 obese nonsurgical controls. At 1 year, subjects who underwent gastric bypass surgery lost 37 ± 2 kg compared with 3 ± 2 kg lost in the nonsurgical controls (p < 0.0001). Spine BMD declined more in the surgical group than in the nonsurgical group whether assessed by DXA (−3.3 versus −1.1%, p = 0.034) or by QCT (−3.4 versus 0.2%, p = 0.010). Total hip and femoral neck aBMD declined significantly in the surgical group when assessed by DXA (−8.9 versus −1.1%, p < 0.0001 for the total hip and −6.1 versus −2.0%, p = 0.002 for the femoral neck), but no changes in hip vBMD were noted using QCT. Within the surgical group, serum P1NP and CTX levels increased by 82% ± 10% and by 220% ± 22%, respectively, by 6 months and remained elevated over 12 months (p < 0.0001 for all). Serum calcium, vitamin D, and PTH levels remained stable in both groups. We conclude that moderate vertebral bone loss occurs in the first year after gastric bypass surgery. However, striking declines in DXA aBMD at the proximal femur were not confirmed with QCT vBMD measurements. These discordant results suggest that artifacts induced by large changes in body weight after bariatric surgery affect DXA and/or QCT measurements of bone, particularly at the hip. © 2014 American Society for Bone and Mineral Research.